Clinical developmental, neuropsychological, and social–emotional features of Turner syndrome. Issue 1 (14th February 2019) - Hutaff‐Lee, Christa; Bennett, Elizabeth; Howell, Susan; Tartaglia, Nicole
Abstract : Individuals with Turner syndrome (TS) are at risk for a constellation of neurocognitive and psychosocial differences, although there is significant individual variability in these features. TS is associated with an increased risk for difficulties with visual–spatial reasoning, visual–spatial memory, attention, executive functioning, motor, and math skills. Additionally, increased rates of social difficulties, anxiety, and depression are observed. There can be significant interplay between all of these factors contributing to the behavioral phenotype. Neuropsychological features and previous research are reviewed. Clinical considerations and recommendations for evaluation and treatment of psychological and behavioral difficulties are provided, including consideration of medical features in TS, as well as therapies, educational supports, and medication treatment. Future research is needed to evaluate effectiveness of different treatments for neuropsychological and psychosocial features of TS, including modification and validation of existing evidence‐based treatments and new approaches to care.